Human Resources in Japanese Industrial Development - Solomon B. Levine, Solomon B. Levine (Princeton University Press, 2014)
THIS monograph deals with the process through which Japan generated human skills and talents required by modern economic activities since the beginning of Japanese industrialization more than a century ago. Because of the vast scope and complexity of the process, the authors decided to focus primarily on institutions established or utilized in major large-scale modern industries that have been leading sectors in Japan's achievement to become the second largest national economy of the world. We have examined these institutions against the background of Japan's overall economic and educational development. However, many other areas of the Japanese industrializing experience deserve treatment that we were unable to include in this study. In narrowing the scope of this work, we wished to concentrate on those large-scale industries that appear to represent the greatest departures and challenges for an agrarian society, such as Japan was in the 1870s, in developing human resources for industrialization. The reader will recognize that this is not the entire story and that a full analysis would include still other large-scale modern industries as well as agriculture and small-scale industrial and commercial sectors. We have not gone deeply into the problems of human resource development that confront Japan at the present time. Rather, our chief concern was to present the historical context in which present-day problems have emerged. This is not to deny the importance of the latter, but it was our belief that an in-depth history of the institutions for generating industrial skills and talents is crucial to understanding the present situation. We began this study about fifteen years ago as part of our ongoing joint work in analyzing the development of the Japanese industrial relations system in the post-World War II period. The opportunity to focus on the historical process of industrial skill generation was facilitated by assistance from the Inter-University Study of Labor Problems in Economic Development, which about that time was redesignated the Inter-University Study of Human Resources in National Development. We are most grateful for the guidance provided by the members of that project, which had embarked upon a wide variety of parallel and complementary studies in this field throughout the world. The help of the Inter-University Study permitted several collaborative research efforts for extended periods by the authors in Japan and the United States.